Stable boundary‐layer regimes at Dome C, Antarctica: observation and analysis. (27th March 2017) - Vignon, Etienne; van de Wiel, Bas J. H.; van Hooijdonk, Ivo G. S.; Genthon, Christophe; van der Linden, Steven J. A.; van Hooft, J. Antoon; Baas, Peter; Maurel, William; Traullé, Olivier; Casasanta, Giampietro
Abstract : Investigation of meteorological measurements along a 45 m tower at Dome C on the high East Antarctic Plateau revealed two distinct stable boundary layer (SBL) regimes at this location. The first regime is characterized by strong winds and continuous turbulence. It results in full vertical coupling of temperature, wind magnitude and wind direction in the SBL. The second regime is characterized by weak winds, associated with weak turbulent activity and very strong temperature inversions reaching up to 25 K in the lowest 10 m. Vertical temperature profiles are generally exponentially shaped (convex) in the first regime and 'convex–concave–convex' in the second. The transition between the two regimes is particularly abrupt when looking at the near‐surface temperature inversion and it can be identified by a 10 m wind‐speed threshold. With winds under this threshold, the turbulent heat supply toward the surface becomes significantly lower than the net surface radiative cooling. The threshold value (including its range of uncertainty) appears to agree with recent theoretical predictions from the so‐called 'minimum wind speed for sustainable turbulence' (MWST) theory. For the quasi‐steady, clear‐sky winter cases, the relation between the near‐surface inversion amplitude and the wind speed takes a characteristic 'S' shape. Closer analysis suggests that this relation corresponds to a 'critical transition' between a steady turbulent and a steady 'radiative' regime, with a dynamically unstable branch in the transition zone. These fascinating characteristics of the Antarctic boundary layer challenge present and future numerical models to represent this region in a physically correct manner.